Alterações do Código Florestal Brasileiro e implicações na conservação de áreas naturais de topos de morros - Ramos, Renata Inês (Universidade Federal de São Carlos, 2018)
Ecosystem services provided by natural areas such, as hydrological and atmospheric regulation, erosion control, pollination and control of agricultural pests, are essential for both the present and future societies, as well as for the sustainability of production systems. Until the year 2012, Brazilian forestry legislation was conducted mainly by Law 4,771 1965, however this law was significantly modified as of the publication of Federal Law 12,651/2012. The change made in the Forest Code has caused profound modifications in two of the most important instruments established by the law: The Permanent Preservation Area – APP and the Legal Reserve – RL. The objective of this study was to analyze the effects generated by the new law with the amendments made in the APP top of hills, mountains and mountain ranges under the responsibility of the São Paulo State Environmental Licensing System in its first four years of application (May / 2012 - May / 2016) and its impact on the conservation of natural resources. For that purpose, the data of authorizations issued by the São Paulo environmental agency in the aforementioned period and in the previous quadrennium (May / 2008 - May / 2012) were compared. The method is based on the tabulation, analysis and critical verification of data from a total of 56 processes that resulted in the issuance of permits for the intervention in the top of hill, mountain and mountain range APP areas by the Sao Paulo environmental agency. In order to represent the data, the sampling units adopted were the Hydrographic Units of Water Resources Management of São Paulo - UGRHI, grouped into four Vocational Units as defined by Law 9,034/1994: agricultural, of conservation, industrialising and industrial. The significant reduction in the number of authorizations issued by CETESB between the two periods clearly indicates that with the substantial decrease in the occurrence of APPs in top of hills, mountains and mountain ranges, the demand for permits for interventions in this APP was also significantly reduced. In this context, it can be con luded that the amendment made by the new law has a potential negative impact on the conservation of natural resources due to the possibility of using and occupying these areas with activities such as agriculture, silviculture and residential, commercial and industrial land subdivision, among others, without any need for authorization, therefore without any control or restriction.
Changes in the Brazilian Forestry Legislation and implications for the conservation of hilltop natural areas
Keywords: Áreas de Proteção Florestal; Gestão Ambiental; Legislação Ambiental; Topos de Morros; Forest Protection Areas; Environmental Management; Environmental Legislation; Hilltops; Recursos naturais - Conservação; Conservation of natural resources; Direito ambiental; Recursos naturais - Legislação; Natural resources - Law and legislation; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::POLITICA E LEGISLACAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS